Antibiotic dispensing patterns and patient interventions for upper respiratory tract infections by hospitals and retail pharmacies: A cross-sectional study based on standardized patients. (March 2021) - Wang, Jing; Gong, Yanhong; Wu, Jianxiong; Jiang, Nan; Chen, Zhenyuan; Yin, Xiaoxv
Abstract: Hospitals and retail pharmacies are the two main sources of antibiotics for the public. This study aimed to compare the antibiotics dispensing patterns between these two types of institutions, and to assess the impact of patient behavior on the dispensing of antibiotics. A cross-sectional survey was conducted in Hubei Province, China, from June 2015 to August 2016. Standardized patients were recruited to simulate upper respiratory tract infections (URTI), presenting three different patient states to physicians and pharmacy staff. We collected a total of 378 cases in hospital and investigated 300 retail pharmacies. Hospitals dispensed a higher proportion of antibiotics compared with retail pharmacies in the cases of no patient intervention (59.50% vs. 33.00%). In the hospitals, compared with non-intervention group, the relative risks of antibiotics dispensing in patient request group was 1.12 (95%CI: 0.93–1.35) and that in patient knowledge expressing group was 0.59 (95%CI: 0.44–0.78). In retail pharmacies, 44.78% of the pharmacies changed the antibiotic dispensing behavior after the patient requested it, whereas 32.32% of the pharmacies no longer sold antibiotics after the patient expressed knowledge. β-Lactam broad-spectrum antibiotics were the most widely distributed drugs in both hospitals and retail pharmacies. The pharmaceutical services provided by hospitals was significantly superior to that of retail pharmacies ( P  < 0.05). The irrational use of antibiotics is common in patients with URTI both in hospitals and retail pharmacies and is susceptible to patients' influence. The quality of pharmaceutical services in both institutions needs to be improved. Highlights: Using standardized patients to investigate both hospitals and pharmacies. The antibiotics dispensing rate is high in hospitals and retail pharmacies. Patients influence the antibiotics dispensing in hospitals and retail pharmacies. β-lactam broad-spectrum antibiotics were the most widely dispensed. The pharmaceutical services provided by hospitals was superior to that of pharmacies.